Impact of Corporate Governance Structures on Firm Performance in China - Wei Tai (Journal of Strategic Management, 2024)
Purpose: The aim of the study was to assess the impact of corporate governance structures on firm performance in China. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Numerous studies have explored the impact of corporate governance structures on firm performance, revealing a complex relationship influenced by various factors. Overall, effective corporate governance mechanisms, such as board independence, CEO duality, and ownership structure, play a significant role in shaping firm performance. Research suggests that firms with independent boards tend to exhibit better performance due to enhanced oversight and strategic decision-making. Conversely, CEO duality, where the CEO also serves as the board chair, can sometimes lead to conflicts of interest and poorer performance. Moreover, ownership structure, particularly the concentration of ownership and the presence of institutional investors, can influence governance effectiveness and subsequently affect firm performance. Additionally, cultural and institutional contexts also mediate the relationship between corporate governance and firm performance, highlighting the need for tailored governance practices in different environments. Overall, while there is no one-size-fits-all approach, establishing robust corporate governance frameworks aligned with organizational objectives can contribute to improved firm performance over the long term. Implications to Theory, Practice and Policy: Agency theory, stakeholder theory and resource dependence theory may be use to anchor future studies on assessing the impact of corporate governance structures on firm performance in China. Practitioners should prioritize enhancing board diversity in terms of gender, ethnicity, professional background, and skillsets to foster broader perspectives and better decision-making processes. Policymakers should implement regulatory reforms that promote best practices in corporate governance, including the adoption of governance codes, disclosure requirements, and compliance standards.